ANALISIS FIQH DAN HUKUM BISNIS ISLAM TERHADAP PENGELOLAAN DANA PENSIUN SYARIAH - Syahrifa Dwi Fitri Fitri; Priyonggo Suseno (Peneliti.net, 2023)
Literacy regarding pension funds in Indonesian society is still very low, where people still think that pension funds are only intended for Civil Servants (PNS) or private employees. In fact, to get a pension is the right of every working citizen so that life in retirement can still be fulfilled. In 2020, 94.35% of working people in Indonesia have not been registered in the pension fund program. One of the efforts made by the Government is to support the formation of a sharia pension fund as a solution for the community to prepare for prosperity in their old age, both in this world and in the hereafter. The purpose of this paper is to determine the basis of fiqh and Islamic business law for the development and management of Islamic pension funds. Because there are differences in the management of conventional pension funds with Islamic pension funds, namely the investment management system carried out to avoid usury and interest-based conventional financial investments. Based on the Fatwa of DSN MUI 88/DSN-MUI/XI/2013 and DSN MUI 99/DSN-MUI/XII/2015 regarding sharia pension funds and sharia annuities, it allows the management of sharia pension funds in accordance with the provisions in the fatwa.